Physical Activity in the Older Adults: A Review of the Benefits and Recommendations for Promoting Healthy Aging through Exercise - Jegarajah Indrakumar; Shehan Silva (Journal of the Indian Academy of Geriatrics)
This literature review examines the advantages of regular physical activity for older individuals, who often experience declines in physical and cognitive capabilities that impact their health and quality of life. Regular exercise has been demonstrated to counteract many age-related negative effects by improving cardiovascular health, including enhanced heart function, increased circulation, and reducing the risk of atherosclerosis and coronary artery disease while promoting longevity. In addition, resistance training is beneficial in preserving muscle mass and strength, which is crucial for maintaining independence and preventing falls. Furthermore, resistance training can improve bone density, preventing osteoporosis, and sarcopenia. Furthermore, physical activity supports brain health by promoting neurogenesis, preventing cerebral atrophy, and enhancing neuroplasticity, which can lead to improved cognition, memory, and executive function. Exercise can also alleviate the symptoms of depression and anxiety, significantly enhancing mental well-being. Virtual group-based exercise programs have been found to effectively reduce depressive symptoms and promote social engagement, combating loneliness and improving emotional well-being. The review emphasizes the extensive benefits of regular physical activity for older adults, including cardiovascular and musculoskeletal health improvements, cognitive function, and mental well-being. It recommends implementing tailored exercise programs and community-based initiatives and using technological tools to encourage and monitor physical activity among older individuals, which is vital for enhancing their quality of life.